The Role of the Subulussalam City Community Care Movement in Instilling Islamic Educational Values among First-Time Voters - Syafnial Syafnial; Abd. Mukti; Salim Salim (Newinera Publisher, 2026)
The increasing number of first-time voters presents both opportunities and challenges for local democracy, particularly in Muslim-majority societies. First-time voters are often vulnerable to unethical political practices due to limited experience and political literacy. This study examines the role of the Gerakan Masyarakat Peduli Kota Subulussalam (GEMAPKOS) in internalizing Islamic educational values among first-time voters in Subulussalam City, Indonesia. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving community leaders, educators, youth participants, and organizational actors. The findings reveal that GEMAPKOS systematically instills core Islamic values such as aqidah, ibadah, akhlak, amanah, shidiq, fathanah, ukhuwah, and responsibility through structured mechanisms, including habituation, role modeling, dialogic learning, social engagement, and formal codification. These processes contribute to the formation of an Islamic political habitus characterized by honesty, critical awareness, discipline, and ethical responsibility in political participation. The study highlights the strategic role of local civil society organizations in bridging Islamic moral education and democratic practice, offering an empirically grounded model for strengthening ethical political participation among first-time voters.